Jurnal OPTIMALISASI PERAN KELUARGA DALAM UPAYA PENCEGAHAN DAN PENANGGULANGAN TINDAK PIDANA BULLYING DAN KDRT DI DESA KWARON - Norma Fitria, Norma Fitria; Faruq, Ahmad; Islami, Trinah Asi; H Noho, Muhammad Dzikrullah; Akbar, Muchammad Fadh; Dardiri, Mashudan; Muhammad, Muhammad (ABIDUMASY, 2024)
Abstrak The Legal Awareness Family Program (KADARKUM) in Kwaron Village, Jombang Regency, aims to enhance community legal awareness, particularly in preventing bullying and Domestic Violence (KDRT). A juridical-sociological research method was used to understand community interactions with legal norms. The program included legal counseling, the provision of Legal Aid Post (POSBAKUM) services, and the formation of Anti-Bullying and Domestic Violence Ambassadors. The results showed increased community understanding of legal rights and obligations, high enthusiasm during counseling sessions, and strong community support for the implemented program. Through this approach, KADARKUM successfully fostered legal awareness at the family level, which is expected to contribute to reducing violence cases in society.